British medicine in an age of reform - French, R. K. (Roger Kenneth); Wear, A. (Andrew), 1946- (Wellcome Institute series in the history of medicine., 1991)
Between 1780 and 1850 was one of the great turning points in British medicine. The authors chart the nature and dynamics of the radical changes which occurred in this period.